Studi Ketahanan Pangan dalam Menjaga Kemandirian Pangan di Kecamatan Kulo: Study of Food Security in Maintaining Food Independence in Kulo District - Zaenal,; Chaeruddin, Zulkarnain; Ahmad, Asmita (Jurnal Ecosolum, 2025)
Food is a basic need that must always be met. As a country with relatively high population growth, Indonesia cannot escape the threat of the global food crisis. This is due to the increasing population growth rate, resulting in higher food consumption by the community. The aim of this research is to study food security in Kulo District using a land intensification approach, in this case fertilization and water management. This research was carried out using the tiling method in calculating productivity rates and carrying out N, P, and K analysis on soil samples to determine the level of fertility in rice fields and to estimate the projected productivity of rice fields using exponential equations so that it can project the results of rice field productivity up to the year 2045. The population growth rate in Kulo District from 2025 to 2045 is 2,06%. The highest population projection result is in 2045, reaching 15.450,59 people, with a per capita consumption of 81,044 kg per person per year in Kulo District. In calculating the rate of productivity of rice fields in Kulo District, it has decreased by 0,043%, with the lowest productivity recorded in 2045 at 32.146 kg ha-1, which is still sufficient to meet the food needs of the people in Kulo District. The highest N content analysis results were found in U1 (0,44%). The highest P analysis results were found in U5 (14,92 ppm). The highest K nutrient content was in sample U4 (0,26). Food conditions in Kulo District are still classified as surplus; however, there are problems with the fertility conditions in the rice fields. Therefore, efforts are needed to increase the fertility of the rice fields in terms of fertilization and water use.